Occurrence and seasonality of Gyrodactylus salaris and G. salmonis (Monogenea) on Arctic char (Salvelinus alpinus (L.)) in the Fustvatnet lake, Northern Norway. Issue 4 (4th January 2023) - Mo, Tor Atle; Hansen, Haakon; Hytterød, Sigurd
Abstract: Gyrodactylus spp. (Monogenea) were found on 16.9% (233 out of 1376) Arctic char, Salvelinus alpinus (L.), sampled from September 2010 to October 2011 in the Fustvatnet lake, Northern Norway. Two species were identified: G. salaris Malmberg, 1957, and G. salmonis Yin & Sproston, 1948. Gyrodactylus salaris was only found on Arctic char larger than 28 cm and only in samples obtained in the autumn (September and October). Gyrodactylus salmonis was found on Arctic char of all sizes (11–47 cm) and throughout the year, with a small peak in abundance in the late autumn (November). Gyrodactylus salaris was found to prefer the tail and dorsal fin. Based on the results, we recommend that surveys of Arctic char for the presence of G. salaris are based on the examination of the fins of large fish sampled during the spawning season (autumn).